Influence of isotacticity and its distribution on degradation behavior of polypropylene. (September 2017) - Chammingkwan, Patchanee; Yamaguchi, Fumitaka; Terano, Minoru; Taniike, Toshiaki
Abstract: The influence of isotacticity and its distribution on the degradation behavior of polypropylene (PP) was examined on a series of PP fractions prepared with the aid of temperature rising elution fractionation technique. It was found that the length of the isotactic sequence predominantly decided the stability of PP fractions, where a faster propagation of oxidation occurred for PP chains with a longer isotactic sequence. Two PP fractions with different tacticity were mixed as the simplest model of polymer to examine the degradation behavior when the primary structure is distributed. It was found that even if two samples have the same average mesopentad, the details of the constituent differentiate their stability, which can be explained as a consequence of infectious degradation spreading.